Cinema novo a partir da perspectiva de gênero : as mulheres em os cafajestes, os fuzis e os deuses e os mortos (Ruy Guerra/1962/1965/1970) - Severo, Carolina Asti (2021)
Throughout the first half of the 1960s, aiming at films focused on the critique of brazilian reality and made using an innovative language, Cinema Novo revolutionized national cinema. Cinema Novo was a cinematographic movement formed mainly by white men of the middle class and upper middle class, located in Rio de Janeiro. Contemporary to the "sexual revolution" and the strengthening of feminisms, the movement did not have the social condition of women as a problem. A historical analysis, from a gender perspective, on how female characters were inserted in the cinemanovista narratives, allow to identify which form the members of the movement understood women within the brazilian reality that they sought to portray. In this way, this dissertation has as objects and sources the three films that Ruy Guerra directed and scripted as a cinemanovista: Os cafajestes (1962), Os fuzis (1965) and Os deuses e os mortos (1970). The general objective is to identify, through the analysis of how women are inserted in the narrative, testimonies about the gender relations and the gender arrangements of the period. As specific objectives, we aim to investigate how the scenes of rape and sexual violence are made and in what context they occur; and in view of Cinema Novo's refusal of the Hollywood formula, assess whether Ruy Guerra's female characters are constructed as a counterpoint to those of Classic Cinema. Based on the feminist theory of cinema, film analysis is used to analyze the films. At the end of the research, it is possible to notice that the three films follow the patriarchal logic inherent to the gender order of brazilian society at the time.